2013
DOI: 10.1080/15438627.2012.757228
|View full text |Cite
|
Sign up to set email alerts
|

The Age-Related Performance Decline in Ultraendurance Mountain Biking

Abstract: The age-related changes in ultraendurance performance have been previously examined for running and triathlon but not mountain biking. The aims of this study were (i) to describe the performance trends and (ii) to analyze the age-related performance decline in ultraendurance mountain biking in a 120-km ultraendurance mountain bike race the "Swiss Bike Masters" from 1995 to 2009 in 9,325 male athletes. The mean (±SD) race time decreased from 590 ± 80 min to 529 ± 88 min for overall finishers and from 415 ± 8 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
4
8
1
1
Order By: Relevance
“…Our data are also consistent with the finding that the decline in cycling performance in triathlon was not significant until the age of ~55 years [27]. However, the age-related decline in performance in 24-h road cycling appears to start later compared with a 120 km endurance mountain cycling race where a significant decline in performance was observed after the age of ~35 years [24]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data are also consistent with the finding that the decline in cycling performance in triathlon was not significant until the age of ~55 years [27]. However, the age-related decline in performance in 24-h road cycling appears to start later compared with a 120 km endurance mountain cycling race where a significant decline in performance was observed after the age of ~35 years [24]. …”
Section: Discussionsupporting
confidence: 90%
“…There were also studies focusing on the influence of age and sex on running performance [18-20], however, only a few studies investigated other endurance disciplines such as swimming [21,22] or cycling [23,24]. Cycling as a non-weight-bearing activity represents an interesting model because it can be performed even in older ages [7] because of its non-technical and its non-weight-bearing character [25].…”
Section: Introductionmentioning
confidence: 99%
“…The finding of an increased participation of master athletes was verified by other authors in marathon running and ultramarathon running 3,510. Other endurance competitions held in ultraswimming,11–14 ultracycling,1519 and ultratriathlons started in the late 20th century 2022…”
Section: Introductionsupporting
confidence: 62%
“…Dla po rów na nia Haupt i wsp. [18] wyka za li, że wy trzy ma łość uczest ni ków star tu ją cych na dłu gim dy stan sie ma le je wraz z wie kiem. Au to rzy w latach 1995-2009 pro wa dzi li ba da nia wśród uczest ni ków szwaj car skie go ma ra to nu ro we rów gór skich, od by wają ce go się na dy stan sie 120 km.…”
Section: The Relationship Between Category Of Competition and The Runclassified
“…Short-and mid-distance was often chosen by older participants. For comparison, Haupt et al [18] demonstrated that endurance decreases with age of participants competing in long-distance races. Between 1995 and 2009 the authors conducted a stu dy among participants of the Swiss mountain biking marathon held over a distance of 120 km.…”
Section: Wnio Skimentioning
confidence: 99%